An RF-MEMS-Based Digitally Tunable SIW Filter in X-Band for Communication Satellite Applications - Abbas El Mostrah; Andrei Muller; Jean-François Favennec; Benjamin Potelon; Alexandre Manchec; Eric Rius; Cédric Quendo; Yann Clavet; Francis Doukhan; Johann Le Nezet (Applied Sciences, 2019)
This paper presents a digitally tunable SIW (substrate integrated waveguide) filter designed for X-band, based on RF-MEMS (radio frequency micro-electrical-mechanical systems) technology. Four commercial off-the-shelf RF-MEMS single-pole single-throw (SPST) switches were directly mounted on the upper surface of the filter, with metallic tuning posts specifically located within each cavity to define the potential achievable frequency range. Fabricated on standard alumina substrate, the design of the filter and the biasing network enabled fine digital frequency control of up to four functional states by the inclusion of wire bondings between each switch and the substrate. A relative tuning range of 2.3% was achieved between the lower and upper discrete states of 2.76% and 2.89% in the 3 dB fractional bandwidths.